Distinct human skeletal muscle-derived CD90 progenitor subsets for myo-fibro-adipogenic disease modeling and treatment in multiplexed conditions - Li, Angela; Anbuchelvan, Madhavan; Fathi, Amir; Abu-Zahra, Maya; Evseenko, Denis; Petrigliano, Frank A.; Dar, Ayelet (Frontiers in Cell and Developmental Biology, 2023)
Chronic muscle injuries, such as massive rotator cuff tears, are associated with progressive muscle wasting, fibrotic scarring, and intramuscular fat accumulation. While progenitor cell subsets are usually studied in culture conditions that drive either myogenic, fibrogenic, or adipogenic differentiation, it is still unknown how combined myo-fibro-adipogenic signals, which are expected to occur in vivo, modulate progenitor differentiation. We therefore evaluated the differentiation potential of retrospectively generated subsets of primary human muscle mesenchymal progenitors in multiplexed conditions in the presence or absence of 423F drug, a modulator of gp130 signaling. We identified a novel CD90+CD56- non-adipogenic progenitor subset that maintained a lack of adipogenic potential in single and multiplexed myo-fibro-adipogenic culture conditions. CD90-CD56- demarcated fibro-adipogenic progenitors (FAP) and CD56+CD90+ progenitors were typified as myogenic. These human muscle subsets exhibited varying degrees of intrinsically regulated differentiation in single and mixed induction cultures. Modulation of gp130 signaling via 423F drug mediated muscle progenitor differentiation in a dose-, induction-, and cell subset-dependent manner and markedly decreased fibro-adipogenesis of CD90-CD56- FAP. Conversely, 423F promoted myogenesis of CD56+CD90+ myogenic subset, indicated by increased myotube diameter and number of nuclei per myotube. 423F treatment eliminated FAP-derived mature adipocytes from mixed adipocytes-FAP cultures but did not modify the growth of non-differentiated FAP in these cultures. Collectively, these data demonstrate that capability of myogenic, fibrogenic, or adipogenic differentiation is largely dependent on the intrinsic features of cultured subsets, and that the degree of lineage differentiation varies when signals are multiplexed. Moreover, our tests performed in primary human muscle cultures reveal and confirm the potential triple-therapeutic effects of 423F drug which simultaneously attenuates degenerative fibrosis, fat accumulation and promotes myo-regeneration.